2017
DOI: 10.3122/jabfm.2017.03.160129
|View full text |Cite
|
Sign up to set email alerts
|

Patient Beliefs Have a Greater Impact Than Barriers on Medication Adherence in a Community Health Center

Abstract: Purpose: Nonadherence to medicines contributes to poor health outcomes, especially for patients with complicated medicine regimens. We examined adherence among patients at a family health center and the impact that barriers to getting medicines and negative beliefs about medicines have on adherence.Methods: A survey was administered incorporating the 8-item Morisky Medication Adherence Scale, questions from the Beliefs about Medicine Questionnaire, and questions about patients' external barriers to getting med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 17 publications
1
32
0
1
Order By: Relevance
“…In contrast, psychological factors such as medication beliefs and patients' perceptions about disease and medications were, however, briefly investigated by only two studies. Yet, previous studies on chronic medication adherence have shown that these behaviour perceptions are better predictors of adherence than socio‐demographic factors . We therefore propose that psychological factors be included when assessing potential correlates of PMN given their potential significance.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, psychological factors such as medication beliefs and patients' perceptions about disease and medications were, however, briefly investigated by only two studies. Yet, previous studies on chronic medication adherence have shown that these behaviour perceptions are better predictors of adherence than socio‐demographic factors . We therefore propose that psychological factors be included when assessing potential correlates of PMN given their potential significance.…”
Section: Discussionmentioning
confidence: 99%
“… 6 7 One of the biggest factors affecting concordance is the patient’s personal belief about the disease and medications. 8 Studies have shown that in order to improve adherence with DMARDs, clinicians should focus less on provision of medical information and be more aware of patients’ beliefs. 9 Understanding patient beliefs however is difficult and often relies on qualitative studies which are excellent at providing an in-depth thematic analysis of a specific issue, but are traditionally conducted on a small scale.…”
Section: Introductionmentioning
confidence: 99%
“…8 Thus, general questions such as, "What keeps you from taking the medicine?," "What would get you to take the medicine?," or "How do you feel about this medicine?" may assist in determining the real reasons people are not taking prescribed medications.…”
Section: Decision: Recognize the Real Reasons/beliefs Behind Patient mentioning
confidence: 99%